Estimation of an Eucalyptus Hybrid (E.grandis x E.urophylla) fuel Wood as a biomass source for the 10 MW Malaysia Dendro power generation plant - bin Muhamad, Mohd Izhwan; Hizam, Hashim; Radzi, Mohd Amran Mohd; Othman, Mohammad Lutfi; Gomes, Chandima; Abdu, Arifin (Penerbit UTHM, 2024)
This research presents the potential of Eucalyptus hybrid tree species as commercial energy crops to support the operation of Dendro power plants in Malaysia. Fuelwood is used in dendro-power plants to generate electricity. With the improvement of modern technology in electricity generation from natural sources and renewable energy sources, the use of wood in Dendro power plants is more effective, durable, environmentally friendly, and sustainable. A sample of Eucalyptus hybrid fuelwood was analyzed to determine if it could be used as a commercial energy crop in Malaysia. The moisture content and calorific value of Eucalyptus hybrids were also tested and calculated. The moisture content of the Eucalyptus hybrid wood samples averaged 11%. The calorific value of the Eucalyptus hybrid wood samples averages 17.06 MJ/kg. In this study, the Eucalyptus hybrid yield per unit energy crop area was estimated specifically for the operation of a 10 MW Dendro power plant. The development of a 10 MW Dendro power plant is expected to generate 50 GWh of electricity per year. This study uses a quantitative approach to estimate the fuelwood resource requirements to operate a Dendro power plant, which has never been done before. Calculations have shown that up to 32,482 tons of Eucalyptus hybrid fuelwood will be needed per year to generate electricity. An estimated 768,834 Eucalyptus hybrid trees will need to be planted and prepared for felling to generate electricity at the Dendro power plant. Finally, it is expected that an area of 706 hectares of land will be required to plant Eucalyptus hybrid trees to be used as commercial energy crops to generate electricity at the Dendro power plant. © This is an open access article under the CC BY-NC-SA 4.0 license.